The Ca2+/calmodulin2‐binding transcription factor TGA3 elevates LCD expression and H2S production to bolster Cr6+ tolerance in Arabidopsis. (26th July 2017) - Fang, Huihui; Liu, Zhiqiang; Long, Yanping; Liang, Yali; Jin, Zhuping; Zhang, Liping; Liu, Danmei; Li, Hua; Zhai, Jixian; Pei, Yanxi
Summary: Heavy metal (HM) contamination on agricultural land not only reduces crop yield but also causes human health concerns. As a plant gasotransmitter, hydrogen sulfide (H2 S) can trigger various defense responses and help reduce accumulation of HMs in plants; however, little is known about the regulatory mechanisms of H2 S signaling. Here, we provide evidence to answer the long‐standing question about how H2 S production is elevated in the defense of plants against HM stress. During the response of Arabidopsis to chromium (Cr 6+ ) stress, the transcription of L‐cysteine desulfhydrase (LCD), the key enzyme for H2 S production, was enhanced through a calcium (Ca 2+ )/calmodulin2 (CaM2)‐mediated pathway. Biochemistry and molecular biology studies demonstrated that Ca 2+ /CaM2 physically interacts with the bZIP transcription factor TGA3, a member of the 'TGACG'‐binding factor family, to enhance binding of TGA3 to the LCD promoter and increase LCD transcription, which then promotes the generation of H2 S. Consistent with the roles of TGA3 and CaM2 in activating LCD expression, both cam2 and tga3 loss‐of‐function mutants have reduced LCD abundance and exhibit increased sensitivity to Cr 6+ stress. Accordingly, this study proposes a regulatory pathway for endogenous H2 S generation, indicating that plants respond to Cr 6+ stress by adjusting the binding affinity of TGA3 to the LCD promoter, which increases LCD expression and promotes H2 S production. This suggests that manipulation of the endogenous H2 S level through genetic engineering could improve the tolerance of grains to HM stress and increase agricultural production on soil contaminated with HMs. Significance Statement: As an important gasotransmitter, H2 S may have many functions in plants; however, knowledge regarding the regulation of endogenous H2 S generation is extremely limited. In this study, we identified a regulatory pathway for endogenous H2 S emission mediated by Ca 2+ /CaM2–TGA3 during the defense of Arabidopsis against Cr 6+ stress. This represents a large step toward understanding H2 S signaling and suggests a potential way to improve the tolerance of grains to HM stress.